THE IMPACT OF COVID-19 ON THE INDICATORS OF A RESEARCH ETHICS COMMITTEE - Quirino da Costa, Patricia; Rodrigues Alves, Albertisa; Ribeiro Santiago, Fred; Sousa da Silva, Anna Paula; Ribeiro Braquehais, Adna; Fernandes Peixoto, Socorro Leticia (Cadernos ESP, 2021)
Objective: To evaluate the impact of COVID-19 on the performance indicators of the Research Ethics Committee of Hospital Geral de Fortaleza. Methods: Retrospective cohort study using the performance indicators from March 2019 to February 2021. Data collection was carried out in April 2021 after approval, under opinion number 4.650.300. Results: In the period from March2019 to February 2020, 433 substantiated opinions were prepared, whereas in the period from March 2020 to February 2021, 439 opinions were recorded. Among the 279 projects considered, 92% contained different themes. Twenty-two projects (8%) were relatedto COVID-19. Conclusion: The findings that the impact of COVID provoked, guide the performance of the management and the members of this Committee with the research activities developed in Fortaleza, suggesting a positive impact on the proactivity of the management and the members of this collegiate.